2012
DOI: 10.1016/j.cell.2012.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Kinase and Phosphatase Activities by Lem4 Enables Nuclear Envelope Reassembly during Mitosis

Abstract: Mitosis in metazoa requires nuclear envelope (NE) disassembly and reassembly. NE disassembly is driven by multiple phosphorylation events. Mitotic phosphorylation of the protein BAF reduces its affinity for chromatin and the LEM family of inner nuclear membrane proteins; loss of this BAF-mediated chromatin-NE link contributes to NE disassembly. BAF must reassociate with chromatin and LEM proteins at mitotic exit to reform the NE; however, how its dephosphorylation is regulated is unknown. Here, we show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
211
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(228 citation statements)
references
References 44 publications
16
211
1
Order By: Relevance
“…Of note, unlike its human homolog, LEM-4 has neither a LEM domain nor a transmembrane domain, and hence it is considered a LEM4-like protein. Antibodies against LEM-4 revealed that it is enriched at the NE (Asencio et al 2012). What regulates LEM-4 so that it desphosphorylates BAF-1 only when chromosome segregation is completed is an interesting and unresolved question.…”
Section: Ne Reassemblymentioning
confidence: 99%
See 3 more Smart Citations
“…Of note, unlike its human homolog, LEM-4 has neither a LEM domain nor a transmembrane domain, and hence it is considered a LEM4-like protein. Antibodies against LEM-4 revealed that it is enriched at the NE (Asencio et al 2012). What regulates LEM-4 so that it desphosphorylates BAF-1 only when chromosome segregation is completed is an interesting and unresolved question.…”
Section: Ne Reassemblymentioning
confidence: 99%
“…BAF-1 is phosphorylated by the VRK-1 kinase (Gorjanacz et al 2007) and this reduces its affinity to DNA. This phosphorylation is reversed by the PP2A phosphatase (Asencio et al 2012).…”
Section: Components Of the Nementioning
confidence: 99%
See 2 more Smart Citations
“…The NE contains many integral proteins (23-26) that participate in genome management or NE reassembly (25,27,28). Emerin is a NE inner membrane protein that interacts with A-and B-type lamins to mediate the anchorage of NE to cytoskeleton (29) and to regulate gene transcription by binding to other chromatin-remodeling molecules such as β-catenin or barrier-to-autointegration factor…”
mentioning
confidence: 99%